Penggunaan Konjungsi Koordinatif pada Karangan Narasi Pengalaman Pribadi Siswa Kelas VII SMP Negeri 3 Kupang Tahun Pelajaran 2025/2026 - Oserla Indrinita Naru; John Darwis Fallo; Ronni M. Ndun; Richard Oematan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to describe students' ability in using coordinate conjunctions in personal experience narrative essays. This study employs a descriptive method with a qualitative approach. Data collection techniques were carried out through the assignment of writing personal experience narrative essays, which were then analyzed based on scoring guidelines covering five aspects, namely accuracy of meaning, organization/structure, variation of conjunctions, application of punctuation, and coherence of the story. The subjects of this study were 32 students of SMP Negeri 3 Kupang City, consisting of 17 males and 15 females. The results of this study indicate that students' ability in using coordinate conjunctions is still varied. In the aspect of accuracy of meaning, some students have been able to use conjunctions appropriately, but there are still students who use conjunctions excessively, thereby obscuring the meaning of sentences. In the aspect of organization/structure, most students have been able to compose sentences coherently, although sentences that are too long and less effective are still found. In the aspect of variation of conjunctions, some students are still limited in their use of conjunction types, which are dominated by the use of the conjunction "and." In the aspect of punctuation application, several errors are still found in the use of commas (,) and periods (.) which cause the delivery of ideas to become less structured. Meanwhile, in the aspect of story coherence, some students have been able to arrange the storyline in a coherent and logical manner, but the meaningful relationships between sentences in the story still need to be strengthened so that the storyline becomes more cohesive. In terms of percentages, students who obtained scores in the very good category were 11 students (34.4%), the good category were 7 students (21.9%), the fairly good category were 8 students (25%), and the poor category were 6 students (18.8%). The average score they obtained was 73. Thus, the use of coordinate conjunctions in personal experience narrative essays among seventh-grade students of SMP Negeri 3 Kupang City falls into the good category.